Dietary water intake and bladder cancer risk: An Italian case–control study. (December 2016) - Di Maso, Matteo; Bosetti, Cristina; Taborelli, Martina; Montella, Maurizio; Libra, Massimo; Zucchetto, Antonella; Turati, Federica; Parpinel, Maria; Negri, Eva; Tavani, Alessandra; Serraino, Diego; Ferraroni, Monica; et al.
Highlights: Investigating the relation between water intake and bladder cancer risk. Total water intake includes water from both beverages and foods. Total water intake was not associated with bladder cancer risk. Some specific water sources were associated with bladder cancer risk. Other components of beverages and foods may be responsible for these associations. Abstract: Previous studies on the relationship between fluid intake and risk of bladder cancer have generally focused on beverages, and results have been inconsistent. We investigated the relationship between water intake and bladder cancer risk, considering water from both beverages and foods. Between 2003 and 2014 we conducted a multicenter hospital-based case–control study in Italy on 690 cases and 665 frequency-matched controls. Water intake for beverages and foods was computed using the Italian food composition database. Odds ratios (ORs) and the corresponding 95% confidence intervals (95%CIs) for water intake were estimated by unconditional multiple logistic regression models, adjusting for major risk factors for bladder cancer. In the control group, the 64.7% of water intake derived from beverages and 35.4% from foods. Comparing the highest with the lowest quartile of intake, water from beverages (OR = 1.14; 95%CI: 0.82–1.59) and water from foods (OR = 0.88; 95%CI: 0.61–1.28) were not significantly associated with bladder cancer risk. Some specific water sources showed significant associations with bladder cancer risk (e.g. water from vegetables, OR = 0.58; 95%CI: 0.40–0.86). However, these associations may be due to the effect of other components contained in beverages and foods rather than to the water content itself. Considering the intakes of water from both beverages and foods, total water intake was not associated with bladder cancer risk.